2015
DOI: 10.1016/j.clinbiomech.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and positional changes of the carpal arch and median nerve during wrist compression

Abstract: Background The carpal tunnel is a fibro-osseous structure containing the median nerve and flexor tendons. Its cross-sectional area has been shown to increase during compressive force application to the carpal bones in modeling and in vitro studies. The purpose of this study was to investigate the morphological and positional changes of the carpal arch and median nerve while in vivo compressive force was applied in the radioulnar direction across the wrist. Methods Ultrasound images of the carpal tunnel and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 24 publications
5
36
2
2
Order By: Relevance
“…The increases in volar area and total CSA with force directed at radial-volar direction was 14.7 and 11.4 mm 2 , respectively. These results are consistent with a previous in-vivo study which showed that 10 N of transverse compressive force results in a volar area increase of 5.65 mm 2 (Marquardt et al, 2015). Similarly, another in vivo study evaluating the pinching of the index finger against thumb reported a decrease of 0.8 mm in CAW and an increase of 5.1 mm 2 in volar area (Shen and Li, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The increases in volar area and total CSA with force directed at radial-volar direction was 14.7 and 11.4 mm 2 , respectively. These results are consistent with a previous in-vivo study which showed that 10 N of transverse compressive force results in a volar area increase of 5.65 mm 2 (Marquardt et al, 2015). Similarly, another in vivo study evaluating the pinching of the index finger against thumb reported a decrease of 0.8 mm in CAW and an increase of 5.1 mm 2 in volar area (Shen and Li, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…CAW values during widening always remained lower than the length of the TCL itself, indicating the TCL did not assume a tensioned state. Narrowing of CAW has been shown to increase the volar area of the carpal tunnel in previous biomechanical studies (Li et al, 2013; Marquardt et al, 2016; Marquardt et al, 2015). The reduction in CAW was maximized in radial volar direction (at 138° from 25.1 to 24.4 mm).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations